Peran Multivitamin terhadap Pertumbuhan dan Kesehatan Rambut: Literature Review - Nabila Ayu Imani; Hapsari Triandriyani; Hadi Firmansyah S (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Hair health is influenced by genetic, hormonal, environmental, and nutritional factors. Hair follicles have high metabolic activity that depends on adequate macro- and micronutrient supply. In recent years, multivitamin use has increased as a strategy to maintain hair health; however, its effectiveness and the risk of over-supplementation remain debated. This paper is a literature review of scientific articles, randomized controlled trials (RCTs), systematic reviews, and meta-analyses published within the last five years. Literature searches were conducted through PubMed, ScienceDirect, and Google Scholar using the keywords hair growth, multivitamin, nutrition, alopecia, supplementation. Macronutrients such as proteins (cysteine, methionine) and essential fatty acids play crucial roles in keratinization and follicular integrity. Micronutrients such as B-complex vitamins, vitamins D, A, C, and E, and minerals like zinc, iron, and selenium act as metabolic cofactors and antioxidants. Clinical evidence shows that multivitamin supplementation improves hair density and quality in individuals with suboptimal nutritional status, although excessive intake of vitamin A and selenium may trigger alopecia. Multivitamins are a promising adjunct therapy to support hair growth and health, especially in individuals with nutritional deficiencies. Their use should be rational, well-measured, and evidence-based to ensure optimal benefits while minimizing the risk of toxicity.